Microbial succession and its correlation with the dynamics of flavor compounds involved in the fermentation of Longxi bacon - Qu, Yuling; Yun, Jianmin; Li, Yanhu; Ai, Duiyuan; Zhang, Wenwei (Frontiers in Microbiology, 2023)
Introduction: Longxi bacon is a traditional fermented meat from Gansu province, China. The ripening process of the bacon is crucial for quality and flavor. The aim of this study was to gain deeper knowledges on the bacterial and fungal community diversity and the changes of chemical components including fatty acids and volatile compounds at different time points during the ripening of the bacon and to understand the relationship between microbial profiles and the chemical components related the bacon flavor. Methods: Bacon samples were collected from days 0, 15, 30, 60 and 90. The bacterial and fungal compositions were analyzed with next generation sequencing targeting the 16S rDNA loci for bacteria and ITS loci for fungi. The fatty acids and the volatile components were analyzed by Headspace Solid Phase Micro Extraction followed by Gas Chromatography/Mass Spectrometry (HS-SPME-GC/MS). Results: We found that the abundance of bacteria in bacon was higher than that of fungi, and Psychrobacter, Brochothrix, Phoma and Trichoderma was the dominant bacon’s population. The largest contributors of volatiles were aldehydes, ketones and esters, and the main fatty acids were palmitic, oleic and linoleic acids. Pearson correlation analysis between microbial succession and key flavor substances showed that the production of Longxi bacon flavor is the result of a combination of bacteria and fungi. Ten bacteria genera and six fungi genera were determined as functional core microbiota for the flavor production based their dominance and functionality in microbial community. In addition, bacteria and fungi are involved in the oxidation and hydrolysis of fatty acids during the ripening of bacon, which also contributes to the formation of bacon flavor. Discussion: This study provides a comprehensive analysis of the key microbiota involved in shaping bacon’s distinctive flavor. Here, the results presented should provide insight into the influence of the microenvironment on the microbial community in bacon and lay a foundation for further investigations into the food ecology of bacon.